Report of the Newfoundland seal-fishery from 1863 "the first year of the steamers," to 1894 [electronic resource] - Chafe, Levi G. (Levi George), 1861-1942? ([St. John's, Nfld.? : s.n.], 1894)
Tables. Introduction by Rev. Moses Harvey. Includes advertising matter. Errata. Cover title. Includes index. Electronic reproduction. Mode of access: Internet. 44